2022
DOI: 10.1055/s-0041-1724071
|View full text |Cite
|
Sign up to set email alerts
|

Questionários Disability of the Arm Shoulder and Hand e Michigan Hand: Explorando a responsividade e performance diagnóstica em amostra de pacientes ambulatoriais com e sem queixas nas mãos e punho

Abstract: Resumo Objetivo Verificar se, em uma população adulta com queixa não traumática dos membros superiores, (1) os questionários Disability of the Arm, Shoulder and Hand (DASH, na sigla em inglês) e Michigan Hand Questionnaire (MHQ, na sigla em inglês) estão suscetíveis ao “efeito de teto”, comparando com amostra de não-doentes; (2) determinar pontos de corte de performance diagnóstica e correlação interquestionários para DASH e MHQ em ambas as amostras. Método Estudo prospectivo, comparativo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, Moraes et al reported that the DASH score has 80% sensitivity and 60.3% specificity in identifying cases. 29 Therefore, assessing the diagnostic accuracy of tools in cross-cultural adaptations is suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Moraes et al reported that the DASH score has 80% sensitivity and 60.3% specificity in identifying cases. 29 Therefore, assessing the diagnostic accuracy of tools in cross-cultural adaptations is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Although responsiveness is examined in some studies, statistical indicators such as sensitivity, specificity, and the area under the curve provide more informative data. It is 29 Therefore, assessing the diagnostic accuracy of tools in crosscultural adaptations is suggested. While the reliability and validity of DASH-KU were comparable or higher than other translated versions, some minor differences were observed.…”
Section: Discussionmentioning
confidence: 99%